Four women posing in costumes. - Gordon, John C. (photographer):::Creator::::::::::::
Four women posing in costumes. Woman on left is wearing a wedding gown and veil holding a bouquet of flowers. Two middle women in floor length dresses and hats and the woman on the right is wearing fringed pants and top.